2002
DOI: 10.1152/ajpheart.00595.2001
|View full text |Cite
|
Sign up to set email alerts
|

Myofilament properties comprise the rate-limiting step for cardiac relaxation at body temperature in the rat

Abstract: The majority of studies aimed at characterizing basic contractile mechanisms have been conducted at room temperature. To elucidate the mechanism of cardiac relaxation under more physiological conditions, we investigated contractile function and calcium handling in ultrathin rat cardiac trabeculae. Active developed tension was unaltered between 22.5 and 30.0 degrees C (from 89 +/- 10 to 86 +/- 11 mN/mm(2), P = not significant) but steeply declined at 37.5 degrees C (30 +/- 5 mN/mm(2)). Meanwhile, the speed of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
183
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(212 citation statements)
references
References 30 publications
29
183
0
Order By: Relevance
“…It is well known that lowering the temperature causes a slow down of contractile kinetics, and thus the lower end of the kinetic range is more easily assessed at room temperature. Figure 5 shows data from our previous work in which the same muscles were studied at both room temperature as well as body temperature and, in addition, under a variety of lengths and frequencies at both temperatures (23). Figure 5A shows average values for the same analysis on a wide variety of protocols in rat trabeculae.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that lowering the temperature causes a slow down of contractile kinetics, and thus the lower end of the kinetic range is more easily assessed at room temperature. Figure 5 shows data from our previous work in which the same muscles were studied at both room temperature as well as body temperature and, in addition, under a variety of lengths and frequencies at both temperatures (23). Figure 5A shows average values for the same analysis on a wide variety of protocols in rat trabeculae.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of data presented in this article are derived from muscle studies published in the past 5 yr by our laboratory with or without the help of collaborating laboratories (18,19,21,23,29,36), with the remaining experiments having been conducted for this study specifically. However, the specific data in this article were collected during those studies but were not analyzed or presented in/for those studies.…”
Section: Methodsmentioning
confidence: 99%
“…However, relaxation of the myocardium under loaded conditions as it occurs in vivo is likely governed in a significantly different manner. Several studies indicate that the myofilament properties play a prominent role in governing the rate of myocardial relaxation [9,47]. Moreover, recent work by us [48], and others [38] argues in favor of a significant involvement of the myofilaments in FDAR.…”
Section: Role Of Myofilaments In Fdarmentioning
confidence: 99%
“…A prime example is that rats and mice are reported to have a negative force-frequency response, but this however has recently been shown to be true mainly, or only, for non-physiological conditions. Under near physiological conditions, and within their respective in vivo heart rate range, the FFR in small rodents is slightly positive or nearly flat, but not negative [2,8,9]. There are two main experimental reasons that have led to the still widely held misconception that the FFR is negative in rats and mice.…”
Section: Role Of Experimental Conditions On the Force Frequency Responsementioning
confidence: 99%
“…This force-frequency behavior is determined by both calcium handling and myofilament properties (26). It has been shown that the integrated dynamic balance of the intracellular Ca 2ϩ concentration ([Ca 2ϩ ] i ) is the primary cellular mechanism responsible for the force-frequency relation (FFR) and is determined by sarcoplasmic reticulum (SR) Ca 2ϩ load and Ca 2ϩ flux through the sarcolemma via L-type Ca 2ϩ channels and the Na ϩ -Ca 2ϩ exchanger (13).…”
mentioning
confidence: 99%